Method for preparing concrete curb by utilizing detoxified fly ash and concrete curb

By optimizing the combination of detoxified fly ash with cement, fly ash, and mineral powder to prepare concrete curb stones, the problems of fly ash disposal and curb stone material consumption have been solved, realizing resource utilization and performance improvement.

CN121135281APending Publication Date: 2025-12-16BAOWU GRP ENVIRONMENTAL RESOURCES TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511293525.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2025-12-16

AI Technical Summary

Technical Problem

In existing technologies, the disposal of fly ash from municipal solid waste incineration faces challenges such as insufficient space and environmental risks. Furthermore, traditional curbstone materials consume a large amount of natural resources and lack efficient ways to utilize them.

Method used

Concrete curb stones were prepared by combining detoxified fly ash with cement, fly ash, and mineral powder. By optimizing the raw material ratio and utilizing the high sulfate activating effect in fly ash, the compressive strength and water absorption performance of the concrete curb stones were improved.

Benefits of technology

Effectively dispose of detoxified fly ash, improve resource utilization, enhance the compressive strength and freeze-thaw resistance of concrete curbs, meet building material standards, and achieve environmental and economic benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a method for preparing a concrete curb by using detoxified fly ash and the concrete curb. The concrete curb is prepared from the following raw materials in parts by weight: 200-250 parts of cement; 0-60 parts of fly ash; 50-70 parts of mineral powder; 15 to 60 parts of detoxified fly ash; 1700 to 1900 parts of aggregate; 170 to 200 parts of water; and 2-5 parts of a water reducing agent. The detoxified fly ash can be effectively digested, the resource utilization rate is increased, meanwhile, the compressive strength of the product can be improved, and the water absorption performance and the freeze-thaw resistance both meet the requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of solid waste resource utilization and concrete curbstone preparation technology, and more specifically, to a method for preparing concrete curbstone using detoxified fly ash and the concrete curbstone itself. Background Technology

[0002] Municipal solid waste incineration fly ash (hereinafter referred to as "fly ash") is a residue generated during the incineration of municipal solid waste, containing high concentrations of dioxins, heavy metals, and soluble salts. Improper disposal can severely pollute soil, water bodies, and the atmosphere, endangering ecological security. Currently, the mainstream disposal route for fly ash is "stabilization / solidification + landfill." However, in recent years, landfill capacity has become increasingly strained, and land resource constraints have become more prominent, placing landfill disposal under the dual pressure of insufficient space and increased potential environmental risks. Therefore, seeking safe and efficient disposal and resource utilization methods for fly ash has become an important direction for research and practice both domestically and internationally.

[0003] The "Technical Specification for Pollution Control of Fly Ash from Municipal Solid Waste" (HJ 1134-2020) stipulates that fly ash treated by specific processes and meeting relevant standards can be classified as general industrial solid waste, rather than hazardous waste. Research shows that detoxified fly ash obtained through deep treatment of municipal solid waste incineration fly ash using a combination of processes such as water washing and pyrolysis has leachate concentrations of heavy metals and residual dioxins significantly lower than the national limits, demonstrating technical feasibility for use as a raw material in building material production.

[0004] Curbstones are marker stones placed between road surfaces and other structures, used on the edges of median strips, driveway edges, or outer edges of shoulders in urban roads. Traditional curbstones are mainly made of natural stone or cement-based materials, consuming large amounts of natural resources such as limestone and sand. With the acceleration of urbanization, the demand for curbstones is surging, and the contradiction between this surge and resource and environmental constraints is becoming increasingly prominent. If detoxified fly ash can be used as a raw material to prepare curbstones, it will not only effectively expand the channels for the resource utilization and disposal of fly ash, but also contribute to carbon reduction and emission reduction in the building materials industry by reducing cement usage. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the purpose of this invention is to provide a method for preparing concrete curb stones using detoxified fly ash and the concrete curb stones themselves. This method can effectively dispose of detoxified fly ash and improve resource utilization. Furthermore, by combining detoxified fly ash with cement, fly ash, and mineral powder to prepare concrete curb stones, the compressive strength of the product can be improved, and the water absorption and freeze-thaw resistance properties both meet the requirements.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a concrete curbstone, the raw materials of which are as follows by weight:

[0008]

[0009] Preferably, the cement is P·O42.5 cement with a specific surface area ≥300m². 2 / kg, 28-day compressive strength ≥42.5MPa;

[0010] The fly ash used is Grade I or Grade II fly ash, with a fineness ≤30%, water requirement ≤105%, and strength activity index ≥70%.

[0011] The mineral powder used is S95 grade mineral powder with a specific surface area ≥400m². 2 / kg, 28d activity index ≥95%;

[0012] The detoxified fly ash meets the following requirements: fineness ≤ 45%, water requirement ratio ≤ 115%, stability (Le Chatelier clamp) ≤ 5mm, and 28-day strength activity index ≥ 70%.

[0013] The aggregate includes fine aggregate and coarse aggregate. The fine aggregate is natural sand or manufactured sand with a particle size ≤5mm and a fineness modulus of 2.3 to 2.8. The coarse aggregate is natural crushed stone or recycled aggregate with a particle size of 5mm to 31.5mm and a crushing value of less than or equal to 30%.

[0014] The water-reducing agent is selected from polycarboxylate water-reducing agents, with a solid content ≥20% and a water reduction rate ≥25%.

[0015] Preferably, the detoxified fly ash has a dioxin content ≤50 ng-TEQ / kg and a soluble chlorine content ≤2%.

[0016] The detoxified fly ash contains high levels of sulfate, which are 8-12% by mass of SO3.

[0017] Preferably, the amount of fine aggregate is 40-42% of the total amount of aggregate.

[0018] Preferably, the raw materials are as follows by weight: 235-248 parts cement, 0-40 parts fly ash, 63-67 parts mineral powder, 18-56 parts detoxified fly ash, 1775-1875 parts aggregate, 175-185 parts water, and 2-5 parts water-reducing agent.

[0019] Preferably, the concrete curbstone has an average 28-day compressive strength ≥ 24 MPa, a minimum 28-day compressive strength ≥ 24 MPa; an average 28-day flexural strength ≥ 3.5 MPa, a minimum 28-day flexural strength ≥ 2.8 MPa; a mass loss rate of ≤ 3% after 50 freeze-thaw cycles; and a water absorption rate of ≤ 6%.

[0020] Preferably, the average 28-day compressive strength of the concrete curbstone is 30–52 MPa, and the minimum 28-day compressive strength is 24–50 MPa; the average 28-day flexural strength is 3.5–6 MPa, and the minimum is 3.0–5.5 MPa; the mass loss rate after 50 freeze-thaw cycles is 1.0%–2%, and the water absorption rate is 2.7%–4.0%.

[0021] A second aspect of the present invention provides a method for preparing concrete curb stones as described in the first aspect of the present invention using detoxified fly ash, comprising the following steps:

[0022] S1, weigh out cement, fly ash, mineral powder, detoxified fly ash, water and water-reducing agent according to the raw material ratio of concrete curbstone;

[0023] S2, After mixing the raw materials in step S1, the curbstone mixture is obtained;

[0024] S3. Apply release agent to the inner wall of the curbstone mold, pour the curbstone mixture into the curbstone mold, and vibrate it thoroughly. After demolding, cure and grind to obtain concrete curbstone.

[0025] Preferably, in step S2, during the stirring and mixing process, the stirring speed is ≥45 rpm and the stirring time is 1 to 3 minutes.

[0026] Preferably, in step S3, low-amplitude high-frequency vibration is used during the compaction process, and the mold is removed after 24-28 hours, followed by curing for 28-30 days.

[0027] The effects of this invention are as follows:

[0028] This invention prepares concrete curb stones by combining cement, fly ash, mineral powder, and detoxified fly ash. On the one hand, each cubic meter of concrete curb stone can incorporate 15-60 kg of detoxified fly ash, which can effectively dispose of the detoxified fly ash, reduce its storage space and disposal costs, and improve resource utilization. On the other hand, this invention can leverage the high sulfate activating potential of detoxified fly ash, innovatively optimize the raw material ratio system of concrete curb stones, and increase the average compressive strength of concrete curb stones using fly ash to replace part or all of the fly ash by about 20% after 28 days. Moreover, the water absorption and freeze-thaw resistance properties meet the requirements of the concrete curb stone (JCT 899-2016) standard, demonstrating significant environmental, economic, and engineering application value. Detailed Implementation

[0029] To better understand the above-mentioned technical solutions of the present invention, the technical solutions of the present invention will be further described below in conjunction with embodiments.

[0030] The present invention provides a concrete curbstone, the raw materials of which are as follows by weight:

[0031]

[0032] The proportioning principles of the components in the above raw materials are as follows: Cement, as the core component of cementitious materials, plays a crucial role in the bonding of concrete systems and is the primary contributing factor to determining the strength performance of concrete; fly ash and mineral powder, as auxiliary cementitious materials, can replace part of the cement, reduce costs, and improve the durability of concrete; detoxified fly ash replaces part or all of the fly ash, and through the sulfur-alkali composite activating effect, it improves the 28-day compressive strength of concrete; aggregates are divided into fine aggregates and coarse aggregates. Coarse aggregates are the skeleton supporting components of concrete, while fine aggregates can fill the voids between coarse aggregates; water-reducing agents are mainly used to disperse cement particles and improve the fluidity and workability of concrete.

[0033] P·O42.5 cement with a specific surface area ≥300m² is selected. 2 / kg, 28-day compressive strength ≥42.5MPa;

[0034] The fly ash used should be Grade I or Grade II fly ash, with a fineness of ≤30%, a water requirement of ≤105%, and a strength activity index of ≥70%.

[0035] The mineral powder used is S95 grade mineral powder with a specific surface area ≥400m². 2 / kg, 28d activity index ≥95%;

[0036] The detoxified fly ash must meet the following requirements: fineness ≤ 45%, water requirement ratio ≤ 115%, stability (Redwich clamp) ≤ 5mm, i.e., the distance between the tips of the Redwich clamp pointers is ≤ 5mm, and the 28-day strength activity index is ≥ 70%. The detoxified fly ash contains high sulfates, such as calcium sulfate, and the high sulfate content is 8-12% by mass of SO3. Among them, the dioxin content of the detoxified fly ash is ≤ 50 ng-TEQ / kg, the soluble chlorine content is ≤ 2%, and the heavy metal leaching concentration does not exceed the maximum allowable discharge concentration limit specified in GB8978 "Integrated Wastewater Discharge Standard" (the maximum allowable discharge concentration of Class II pollutants shall be implemented in accordance with the Class I standard).

[0037] The aggregate includes fine aggregate and coarse aggregate. The fine aggregate is natural sand or manufactured sand with a particle size ≤5mm and a fineness modulus of 2.3 to 2.8. The coarse aggregate is natural crushed stone or recycled aggregate with a particle size of 5mm to 31.5mm and a crushing value of less than or equal to 30%. In a preferred embodiment, the amount of fine aggregate is 40% to 42% of the total amount of aggregate.

[0038] The water-reducing agent selected is a polycarboxylate water-reducing agent with a solid content ≥20% and a water reduction rate ≥25%.

[0039] In a specific embodiment, the raw materials are as follows by weight: 235-248 parts cement, 0-40 parts fly ash, 63-67 parts mineral powder, 18-56 parts detoxified fly ash, 1775-1875 parts aggregate, 175-185 parts water, and 2-5 parts water-reducing agent. In a preferred embodiment, the amount of fly ash can be 0.

[0040] The concrete curb stones described above have an average 28-day compressive strength ≥ 24 MPa and a minimum 28-day compressive strength ≥ 24 MPa; an average 28-day flexural strength ≥ 3.5 MPa and a minimum 28-day flexural strength ≥ 2.8 MPa; a freeze-thaw cycle mass loss rate ≤ 3% and a water absorption rate ≤ 6%. In specific embodiments, the concrete curb stones have an average 28-day compressive strength of 30–52 MPa and a minimum 28-day compressive strength of 24–50 MPa; an average 28-day flexural strength of 3.5–6 MPa and a minimum of 3.0–5.5 MPa; a freeze-thaw cycle mass loss rate of 1.0%–2% and a water absorption rate of 2.7%–4.0%.

[0041] This invention also provides a method for preparing the above-mentioned concrete curbstone using detoxified fly ash, comprising the following steps:

[0042] S1, weigh out cement, fly ash, mineral powder, detoxified fly ash, water and water-reducing agent according to the raw material ratio of concrete curbstone;

[0043] S2, After mixing the raw materials in step S1, the curbstone mixture is obtained;

[0044] In this step, the stirring speed is ≥45 rpm and the stirring time is 1 to 3 minutes.

[0045] S3. Apply release agent to the inner wall of the curbstone mold, pour the curbstone mixture into the curbstone mold, and vibrate it thoroughly. After demolding, cure and grind to obtain concrete curbstone.

[0046] In this step, after pouring the curbstone mixture into the curbstone mold, it is vibrated at low amplitude and high frequency for 24-28 hours before demolding. After demolding, it continues to cure in a standard curing room for 27-28 days. After the concrete curbstone has been cured, some parts are ground and then placed on a flat surface to prevent damage such as chipped corners.

[0047] Example

[0048] The following raw materials were used in the preparation of the concrete curbstone in this embodiment:

[0049] P·O42.5 cement with a specific surface area of ​​370 m² was selected. 2 / kg, 28-day compressive strength is 55MPa;

[0050] The fly ash used is Grade II fly ash with a fineness of 3.4%, a water requirement ratio of 94%, and a strength activity index of 72.

[0051] The mineral powder used is S95 grade mineral powder with a specific surface area of ​​420m². 2 / kg, 28d activity index 98%;

[0052] The detoxified fly ash (45μm square hole sieve residue) has a fineness of 43%, a water demand ratio of 108%, a stability (Rayet clamp) of 0.5mm, and a 28-day strength activity index of 72%. This detoxified fly ash contains high levels of sulfates, such as calcium sulfate, with a sulfate content of 11% by mass of SO3. The detoxified fly ash meets the following requirements: dioxin content of 10 ng-TEQ / kg, soluble chlorine content of 0.75%, and heavy metal leaching concentration less than the maximum allowable discharge concentration limit specified in GB8978 "Integrated Wastewater Discharge Standard" (the maximum allowable discharge concentration for Class II pollutants shall be implemented according to the Class I standard).

[0053] The aggregates include coarse aggregates and fine aggregates. The coarse aggregates are natural crushed stone with a diameter of 5-31.5mm and a crushing value of 18%. The fine aggregates are natural medium-grade sand with a particle size of 0-5mm and a fineness modulus of 2.5. The amount of fine aggregates is 40% of the total aggregates.

[0054] The water-reducing agent selected is polycarboxylate water-reducing agent with a solid content ≥20% and a water reduction rate ≥25%.

[0055] The proportions of the above raw materials are shown in Table 1;

[0056] Table 1 Raw material ratio (parts by weight)

[0057]

[0058] The method for preparing concrete curb stones using detoxified fly ash in this embodiment is as follows:

[0059] (1) Weigh out cement, fly ash, mineral powder, detoxified fly ash, water and water-reducing agent according to the raw material ratio shown in Table 1;

[0060] (2) Mix the raw materials in the proportions in Table 1. The mixing speed should be no less than 45 rpm and the mixing time should be 1 to 3 minutes. After mixing, the curbstone mixture is obtained.

[0061] (3) Apply release agent to the inner wall of the curbstone mold, pour the curbstone mixture into the curbstone mold, and vibrate it thoroughly. Use low amplitude high frequency vibration. Demold after 1 day. Then continue to cure in the standard curing room for 28 days and grind some parts to obtain concrete curbstone.

[0062] The concrete curb stones obtained above were subjected to tests for compressive strength, flexural strength, water absorption and frost resistance in accordance with JC / T899-2016 "Concrete Curb Stones" and GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". The results are shown in Tables 2 and 3.

[0063] Table 2. Compressive and flexural strengths of concrete curb stones (MPa)

[0064]

[0065]

[0066] Table 3 Water absorption rate and frost resistance of concrete curb stones

[0067]

[0068] As shown in Table 1, the average 28-day compressive strength of the concrete curb stones prepared in Examples (B, C, D) of this invention is 30.9–33.4 MPa, with a minimum of 24.8–28.5 MPa; the average 28-day flexural strength is 3.5–3.9 MPa, with a minimum of 2.8–3.4 MPa. The 28-day compressive strength of the concrete curb stones prepared in Examples (F, G, H) is 46.0–51.6 MPa, with a minimum of 44.2–50.0 MPa; the average 28-day flexural strength is 4.5–5.7 MPa, with a minimum of 4.2–5.3 MPa. Combined with the blank control groups A and E, it can be seen that under the same conditions of other material dosages and water-cement ratios, replacing part or all of the fly ash with detoxified fly ash increases the average 28-day compressive strength by 20%, and the 28-day flexural strength meets the standard C of curb stones (JCT 899-2016). c 40C f 4.0 or C c 30C f 3.5 Requirements: In Examples D and E, detoxified fly ash replaced all fly ash, and the 28-day compressive strength and 28-day flexural strength of the concrete curbstone concrete prepared under other identical conditions were significantly improved.

[0069] As shown in Table 3, the water absorption rate of the concrete curb stones prepared in Examples (B, C, D) of this invention is 3.6%–3.8%, and the 28-day freeze-thaw resistance (D50 mass loss rate) is 1.5%–1.7%; the water absorption rate of the concrete curb stones prepared in Examples (F, G, H) is 2.7%–3.1%, and the 28-day freeze-thaw resistance (D50 mass loss rate) is 1.0%–1.4%, meeting the requirements of CT 899-2016 "Concrete Curb Stones". In summary, this invention utilizes detoxified fly ash to replace fly ash in the preparation of concrete curb stones, achieving similar water absorption and freeze-thaw resistance. The prepared concrete curb stones have a water absorption rate ≤6% and a 50-cycle freeze-thaw mass loss rate ≤3%, meaning that the concrete curb stones prepared using detoxified fly ash as a substitute for cementitious materials meet the specifications.

[0070] Those skilled in the art should recognize that the above embodiments are merely illustrative of the present invention and are not intended to limit the present invention. Any variations or modifications to the above embodiments that are within the spirit and essence of the present invention will fall within the scope of the claims of the present invention.

Claims

1. A concrete curb, characterized in that, The raw materials are as follows in parts by weight:

2. The concrete curbstone according to claim 1, characterized in that: The cement is P·O42.5 cement, and the specific surface area is greater than 300 m 2 / kg, and the 28-day compressive strength is greater than or equal to 42.5 MPa. The fly ash is selected from I or II grade fly ash, with fineness ≤30%, water demand ratio ≤105%, and strength activity index ≥70%; The mineral powder is S95 grade mineral powder, specific surface area ≥400 m 2 / kg, 28d activity index ≥95%. The detoxified fly ash meets the following requirements: fineness ≤45%, water demand ratio ≤115%, stability (Lea's clamp) ≤5mm, and 28-day strength activity index ≥70%; The aggregate includes fine aggregate and coarse aggregate, the fine aggregate is natural sand or machine-made sand with particle size ≤5mm and fineness modulus 2.3-2.8, and the coarse aggregate is natural crushed stone or recycled aggregate with particle size 5-31.5mm and crushing value ≤30%; The water reducing agent is selected from polycarboxylic acid water reducing agent with solid content ≥20% and water reducing rate ≥25%.

3. The concrete curb of claim 2, wherein: The detoxified fly ash has dioxin content ≤50ng-TEQ / kg and soluble chlorine content ≤2%. The detoxified fly ash contains high sulfate salt, and the content of the high sulfate salt is 8-12% in terms of mass percentage of SO3.

4. The concrete curb of claim 2, wherein, The amount of the fine aggregate is 40-42% of the total amount of the aggregate.

5. The concrete curb of claim 1, wherein, The raw materials are as follows in parts by weight: cement 235-248 parts, fly ash 0-40 parts, mineral powder 63-67 parts, detoxified fly ash 18-56 parts, aggregate 1775-1875 parts, water 175-185 parts, and water reducing agent 2-5 parts.

6. The concrete curb of claim 1, wherein, The 28-day compressive strength of the concrete curbstone is ≥24MPa, the 28-day flexural strength is ≥2.8MPa, the mass loss rate after 50 times of freeze-thaw is ≤3%, and the water absorption rate is ≤6%.

7. The concrete curb of claim 1, wherein, The average 28-day compressive strength of the concrete curbstone is 30-52MPa, the minimum 28-day compressive strength is 24-50MPa, the average 28-day flexural strength is 3.5-6MPa, the minimum 28-day flexural strength is 3.0-5.5MPa, the mass loss rate after 50 times of freeze-thaw is 1.0%-2%, and the water absorption rate is 2.7%-4.0%.

8. A method for producing a concrete curb according to any one of claims 1 to 7 using detoxified fly ash, characterized by, The method comprises the following steps: S1, weighing cement, fly ash, mineral powder, detoxified fly ash, water, and water reducing agent according to the raw material ratio of the concrete curbstone; S2, mixing the raw materials in step S1 to obtain a curbstone mixture; S3, applying release agent to the inner wall of a curbstone mold, pouring the curbstone mixture into the curbstone mold, and fully vibrating, then demolding, curing, and polishing to obtain a concrete curbstone.

9. The method of claim 8, wherein the method further comprises: adding water to the fly ash to form a slurry; and mixing the slurry to form a concrete. In step S2, the stirring speed is ≥45rpm and the stirring time is 1-3min.

10. The method of claim 8, wherein the method further comprises: adding water to the fly ash to form a slurry; and mixing the slurry to form a concrete. In step S3, low-amplitude high-frequency vibration is used during the vibrating process, and the demolding is performed after 24-28h, and the curing is continued for 28-30 days after demolding.

Citation Information

Cited By

  • Preparation method of detoxified fly ash-based high-strength inorganic ecostone

    CN121758138A